AH-6809 mediated regulation of lung adenocarcinoma metastasis through NLRP7 and prognostic analysis of key metastasis-related genes - Feng, Xu; Wu, Wei; Liu, Feifei (Frontiers in Pharmacology, 2024)
Introduction: Lung adenocarcinoma (LUAD) has become one of the leading causes of cancer-related deaths globally, with metastasis representing the most lethal stage of the disease. Despite significant advances in diagnostic and therapeutic strategies for LUAD, the mechanisms enabling cancer cells to breach the blood-brain barrier remain poorly understood. While genomic profiling has shed light on the nature of primary tumors, the genetic drivers and clinical relevance of LUAD metastasis are still largely unexplored. Objectives: This study aims to investigate the genomic differences between brain-metastatic and non-brain-metastatic LUAD, identify potential prognostic biomarkers, and evaluate the efficacy of AH-6809 in modulating key molecular pathways involved in LUAD metastasis, with a focus on post-translational modifications (PTMs). Methods: Genomic analyses were performed using data from The Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus (GEO). Differentially expressed genes (DEGs) between brain-metastatic and non-metastatic LUAD samples were identified. Key gene modules were determined using Weighted Gene Co-expression Network Analysis (WGCNA), and their prognostic significance was assessed through Kaplan-Meier analysis. Cellular experiments, including CCK8 and qRT-PCR assays, were conducted to evaluate the anti-cancer effects of AH-6809 in LUAD cells. Apoptosis and inflammatory marker expression were assessed using immunofluorescence. Results: Genomic analysis differentiated brain-metastatic from non-brain-metastatic LUAD and identified NLRP7, FIBCD1, and ELF5 as prognostic markers. AH-6809 significantly suppressed LUAD cell proliferation, promoted apoptosis, and modulated epithelial-mesenchymal transition (EMT) markers. These effects were reversed upon NLRP7 knockdown, highlighting its role in metastasis. Literature analysis further supported AH-6809's tumor-suppressive activity, particularly in NLRP7 knockdown cells, where it inhibited cell growth and facilitated apoptosis. AH-6809 was also found to affect SUMO1-mediated PTMs and downregulate EMT markers, including VIM and CDH2. NLRP7 knockdown partially reversed these effects. Immunofluorescence revealed enhanced apoptosis and inflammation in lung cancer cells, especially in NLRP7 knockdown cells treated with AH-6809. The regulatory mechanisms involve SUMO1-mediated post-translational modifications and NQO1. Conclusion: These findings demonstrate the critical role of NLRP7 and associated genes in LUAD metastasis and suggest that AH-6809 holds promise as a potential therapeutic agent for brain-metastatic LUAD.